Biosorption of pb (ii) by sulfuric acid treated spent grated coconut (cocos nucifera) (ssgc) in fixed-bed column mode / Norhasyira Hashim - Hashim, Norhasyira (Faculty Of Applied Sciences, 2016)
Spent grated coconut (cocos nucifera) from food industry waste was developed as a new and efficient biosorbent. In this study, the treated spent grated coconut was chosen to be investigated for removing Pb (II) from wastewater. The fixed-bed column study mode was employed under fixed parameters and column condition. The adsorption of adsorbent was investigated by using 1 g of biosorbent at pH 4, and the flow rate of 12 mL/min. The inlet concentrations of 80 mg/L of Pb (ll) was used as initial concentration. The breakthrough curve was establish and two kinetic model were used; Thomas model and Yoon-Nelson model. Both model were fitted to this study with coefficient of correlation value (R2) of 0.871. The column capacity, qb determined from breakthrough curve plot was 67.97 mg/g which was of higher adsorption capacity recorded among plant wastes.